Growth and Characterization of Carbon Nanotubes by Thernal Chemical Vapor Deposition Method - Aksak, Meral; Selamet, Yusuf (Izmir Institute of Technology, 2008)
This thesis work is focused on producing carbon nanotubes (CNTs) by methane gas thermal chemical vapor deposition method on very thin Cobalt, Iron, and Nickel catalyst thin films deposited onto SiO2/Si substrates by DC magnetron sputtering. This thesis is also devoted to understanding some parameters affecting the growth of CNTs; such as catalyst material, temperature, and catalyst layer thickness effects In this study, CNT growth was performed on directly Si substrates, which was observed that the growth was too difficult and requiring very high temperatures. Hence, very thin catalyst films were deposited on SiO2/Si substrates, and the CNT growth was observed. The temperature effect was also examined. When the growth temperature was increased, the average diameters of the CNTs were decreased up to a critical temperature, but after this point the average diameter of CNTs were increased. This effect was studied systematically by utilizing Fe and Co catalyst thin films and with the help of Raman spectroscopy and Scanning Electron Microscopy results.Catalyst thickness effect was also examined. For this aim, Ni catalyst thin films with three different thicknesses; 0.7 nm, 1.4 nm, and 6 nm, were utilized. It was observed that CNTs were grown well on 0.7 and 1.4 nm thick Ni films, while there was a little growth on 6 nm thick Ni film. The roughness analysis of 0.7 nm and 1.4 nm thick Ni films were also done. Some of as-grown CNTs were also examined by X-ray diffraction method, and the results were compared one another.
Thesis (Master)--Izmir Institute of Technology, Physics, Izmir, 2008
Includes bibliographical references (leaves: 53-61)
Text in English; Abstract: Turkish and English
xi, 61 leaves
Keywords: TA418.9.N35 A315 2008; Nanostructured materials; Nanotubes; Carbon; Catalysis